Correlation of porosity and properties of recycled fine aggregate concrete with fly ash - Hangwei Lin; Koji Takasu; Hidehiro Koyamada; Hiroki Suyama (Acta Polytechnica CTU Proceedings)
In this paper, we presented the experimental discussion of samples of recycled aggregate concrete with replacement of natural fine aggregate by recycled fine aggregate. Three mix kinds were produced and, for each of these three kinds, two levels of water to blinder ratio were used with 0%, 10% and 20% of FA. The result of the tests of drying shrinkage and compressive strength of recycled concrete were used for comparison with tests of mercury intrusion porosimetry (MIP), in which the cumulative pore volume and different intervals of pore volume were studied at ages of 28 and 91 days. Correlation graph of compressive strength and cumulative pore volume might be predicted with given W/B, days and FA of the concrete or none given and drying shrinkage might be predicted with given FA.